2007
DOI: 10.1126/science.1138659
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association of De Novo Copy Number Mutations with Autism

Abstract: We tested the hypothesis that de novo copy number variation (CNV) is associated with autism spectrum disorders (ASDs). We performed comparative genomic hybridization (CGH) on the genomic DNA of patients and unaffected subjects to detect copy number variants not present in their respective parents. Candidate genomic regions were validated by higher-resolution CGH, paternity testing, cytogenetics, fluorescence in situ hybridization, and microsatellite genotyping. Confirmed de novo CNVs were significantly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
2,059
12
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,553 publications
(2,190 citation statements)
references
References 30 publications
69
2,059
12
24
Order By: Relevance
“…[35][36][37][38][39][40][41][42][43] Within our associated region, a segmental duplication is reported, 44 which is situated between the two associated regions on the DRB1*0401-DQA1*03-DQB1*0302 haplotypic background and caused a 223-kb gap not genotyped in our study. This segmental duplication has, to our knowledge, not been studied regarding human diseases.…”
Section: Discussionmentioning
confidence: 58%
“…[35][36][37][38][39][40][41][42][43] Within our associated region, a segmental duplication is reported, 44 which is situated between the two associated regions on the DRB1*0401-DQA1*03-DQB1*0302 haplotypic background and caused a 223-kb gap not genotyped in our study. This segmental duplication has, to our knowledge, not been studied regarding human diseases.…”
Section: Discussionmentioning
confidence: 58%
“…These cytogenetic abnormalities are observed in chromosomes 5p15, 15q11–q13, 17p11, and 22q11.2 (Jacquemont et al., 2006; Sebat et al., 2007). Abnormalities affecting the 15q11–q13 region represent the most frequent variation associated with ASD accounting for close to 1% of all ASD cases (Badescu et al., 2016).…”
Section: Reviewmentioning
confidence: 99%
“…Besides structural rearrangements, other abnormalities of chromosomal numbers or aneuploidies are detected in ASD including trisomy 21, Turner syndrome (45, X), and Klinefelter syndrome (47, XXY; Devlin & Scherer, 2012). Thanks to the comparative genomic hybridization (CGH) technique or SNPs array, CNVs were also found in multiple chromosomal regions at 1q21.1, 16p11.2, 17q12, and 22q11.2 (Jacquemont et al., 2006; Marshall et al., 2008; Matsunami et al., 2013; O'Roak et al., 2012; Pinto et al., 2010; Sebat et al., 2007). Further studies supported the association with ASD of two recurrent de novo CNVs at 16p11.2 (duplication and deletion) and 7q11.23 (duplication; Levy et al., 2011; Sanders Stephan et al., 2011).…”
Section: Reviewmentioning
confidence: 99%
“…6,7 New molecular techniques, such as array comparative genomic hybridization (CGH), seem to help increase the rate of genetic diagnosis, particularly in individuals where autism is accompanied by malformations or dysmorphic features. 8 Moreover, the deletions and duplications detected in ASD patients may point to new disease genes involved in non-syndromic cases 9 and it has been shown that functional de novo mutations occur in ASDs at higher frequency than expected. 10 ASD is sometimes associated with fragile X syndrome (MIM #300624), tuberous sclerosis (MIM #191100), and cytogenetically detectable chromosome abnormalities.…”
Section: Introductionmentioning
confidence: 99%